2017
DOI: 10.1186/s40635-017-0146-1
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability in critical care medicine: a systematic review

Abstract: BackgroundHeart rate variability (HRV) has been used to assess cardiac autonomic activity in critically ill patients, driven by translational and biomarker research agendas. Several clinical and technical factors can interfere with the measurement and/or interpretation of HRV. We systematically evaluated how HRV parameters are acquired/processed in critical care medicine.MethodsPubMed, MEDLINE, EMBASE and the Cochrane Central Register of Controlled Trials (1996–2016) were searched for cohort or case–control cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
41
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 75 publications
2
41
0
3
Order By: Relevance
“…Results similar to our results were obtained by S. N. Karmali et al [13], who concluded that a single dose of β 2 -agonist increased the heart rate by 9.12 beats/min and reduced the potassium concentration by 0.36 mmol/L, compared to placebo. For trials lasting from 3 days to 1 year, β 2 -agonist treatment significantly increased the risk for a cardiovascular event (relative risk [RR], 2.54; 95 % CI, 1.59 to 4.05) compared to placebo.…”
Section: Discussionsupporting
confidence: 92%
“…Results similar to our results were obtained by S. N. Karmali et al [13], who concluded that a single dose of β 2 -agonist increased the heart rate by 9.12 beats/min and reduced the potassium concentration by 0.36 mmol/L, compared to placebo. For trials lasting from 3 days to 1 year, β 2 -agonist treatment significantly increased the risk for a cardiovascular event (relative risk [RR], 2.54; 95 % CI, 1.59 to 4.05) compared to placebo.…”
Section: Discussionsupporting
confidence: 92%
“…In ICUs, the major studies have focused on the use of HRV for the prediction of morbimortality. 35 It is traditionally obtained by comparing the R–R intervals in the electrocardiogram, differently from this study, which used the interval between the PPG SPs. Studies have shown that the analysis of the HRV is reliable in individuals at rest and that motion artifacts can contaminate the signal.…”
Section: Discussionmentioning
confidence: 99%
“… 38 The results did not present a significant difference between the groups, as it was expected and shown in other studies, in which a lower HRV is related to a higher sympathovagal imbalance and higher mortality. 35 Perhaps, the very short time in collecting data has influenced such results.…”
Section: Discussionmentioning
confidence: 99%
“…As alterações cardiovasculares podem ser avaliadas de diversas formas, dentre elas, por meio da análise da VFC. O estudo da VFC é um método não invasivo e seletivo que avalia a modulação autonômica102,103 . HF= 0,15-1,2Hz), correspondendo à modulação vaga46 .…”
unclassified
“…Este fator talvez possa ter contribuído para que a VFC não tenha apresentado significância estatística como preditora da falha/sucesso do processo de desmame ventilatório, do TRE e da extubação traqueal. A ausência de estudos prévios em pediatria com número de amostra maior e com análise de subgrupos por doenças/fisiopatologias específicas, dificultam as comparações do comportamento no processo de desmame ventilatório nesta faixa etária46,103 .Em geral, os estudos são baseados em registros de curto prazo da VFC e envolvem grupos heterogêneos com resultados divergentes46,103 . do CO2 exalado devem ser rotina das Unidades de Terapia Intensiva Pediátrica, haja visto que se trata de uma medida não invasiva, de fácil aplicação frente à equipe multiprofissional e que traz informações importantes do paciente pediátrico, como maior risco de falha/ sucesso da extubação traqueal.As limitações econtradas no nosso estudo foram o N pequeno (apenas 43 TRE), além de grupo de pacientes heterogêneo, mesmo quando avaliados apenas o subgrupo de "doenças respiratórias".…”
unclassified